THE YIELD AND CHEMICAL CHARACTERISTICS OF RED SEAWEED EXTRACT (Eucheumaspinosum) - Febriani Melisa Sinurat; Andarini Diharmi; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTSeaweed is a type of algae that can live in marine waters and is the largest part of marine plants. This study aimed to observe the chemical composition of red seaweed (Eucheumaspinosum) originating from the Takalar Waters of South Sulawesi Province. The seaweedE. spinosumextract were evaluated for their chemical characteristics including the content of moisture, ash, protein, and the yield. The results showed that the chemical characteristics ofseaweed extracthad yield, moisture content, ash content and protein content of 5.23%, 21.27%, 1.55% and 5.74%, respectively. Keywords:chemical composition,Eucheumaspinosum, seaweed